Examining the discourse regarding the delivery of occupational infection prevention and control training to healthcare workers: a scoping review of pandemic plans of 23 countries. Issue 8 (24th August 2022) - Qureshi, Mohammmed Owais; Chughtai, Abrar Ahmad; Islam, M Saiful; Tuckerman, Jane; Seale, Holly
Abstract : Background: Over the years, countries reformed their pandemic plans but still healthcare systems were unprepared to handle the COVID-19 pandemic. Throughout the COVID-19 pandemic, healthcare workers (HCWs) raised issues around shortage of personal protective equipment (PPE), inadequate occupational infection prevention and control (IPC) training, lack of guidance regarding reuse/extended use of PPE and absence of HCWs. Objective: The objective of this scoping review was to compare national and transnational pandemic plans and COVID-19 guidelines for the inclusion of recommendations regarding pandemic-specific occupational IPC training for HCWs, as well as strategies for managing the surge in PPE needs and staffing. Inclusion criteria: From each of the six WHO defined world regions, four countries with the highest burden of COVID-19 cases (as of mid-2020) were selected and attempted to locate the relevant pandemic plans and COVID-19 guidelines. Methods: Searches were undertaken of 1: National Guidelines Clearinghouse, 2: websites of international public healthcare agencies such as WHO, the European Centre for Disease Prevention and Control (ECDC) and, 3: in-country health departments/Ministry of Health/Department of Public Health, between June 2020 and July 2021. The data were summarised under six themes drawn from publicly available pandemic plans and COVID-19 (IPC) guidelines of WHO, ECDC and 23 countries. Results: The WHO, ECDC and 14 countries reported pandemic-specific IPC training; however, only four discussed training HCWs on correct PPE use; six countries listed strategies to manage the surge in demand of HCWs, while only five discussed managing the shortage of PPE. None of the COVID-19 guidelines recommended training HCWs for correct reuse or extended use of PPE and only one country's guideline outlined mandatory HCWs attendance and delivery of training in a regional language. Conclusion: Pandemic plans should be revised to include guiding principles regarding the delivery of pandemic specific IPC training. There is also a need to provide guidance on when countries should consider reuse and extended use of PPE. This discourse should also be reflected in disease-specific pandemic guidelines, like COVID-19 (IPC) guidelines. The aim of this review is to assist international health agencies in generating evidence-based guideline updates.